Sturge Weber Syndrome: A Case Report - Kushdeep Kumar Gupta; Hemant Sawhney (Oral Sphere Journal of Dental and Health Sciences, 2025)
Background: Sturge-Weber syndrome is a congenital neurocutaneous disorder characterized by facial port-wine stain, seizures, intellectual disability, glaucoma, etc. After tuberous sclerosis and neurofibromatosis, it is the most prevalent neurocutaneous condition. Case Presentation: A 16-year-old male patient presented with a unilateral port wine stain on the right side of the face and pain in the right side of the eye. On the clinical examination, there was a port-wine stain present extraorally and intraorally, and generalized bleeding on probing from the gingiva. The patient's past medical history revealed glaucoma for 6 years, and he is under medication. Sturge-Weber syndrome consists of ocular, neurological, cutaneous and oral manifestations. The most common manifestation seen on the unilateral side of the face and involves the intra-orally unilateral side. In the present case, there is a glaucoma in the right eye and a port-wine stain on the right side of the eye. Based on the Roach classification, our case fell under Type-I. Conclusion: Sturge weber syndrome requires a multidisciplinary team work and all the treatment are symptomatic, there is no cure for the syndrome. Patient need ophthalmologist for the follow up due to risk of developing glaucoma and the dermatologist for the development of the lesion.